Estrutura da comunidade bêntica do Parque Estadual Marinho de Areia Vermelha, Cabedelo (PB): avaliação dos efeitos do turismo na macrofauna local - Schimith, Laís Gumier (2019)
The marine environment has been suffered many impacts associated to environmental condition changes and by the crescent expansion of the tourism. The damage associated to recreational activities on leisure and vacation popular destinations such as the “Parque Estadual Marinho de Areia Vermelha” (PEMAV; Red Sand Marine State Park) is even more intense. This study has aimed to characterize the benthic macrofauna and identify possible impacts after the high visitation season (summer). Following the BACI (before-after-controlimpact) outline, samplings have been performed on November 2017 and March 2018 (before and after the high visitation season). Triplicate samples were taken in the sublittoral and intertidal zones at Areia Dourada (AD; reference area) and four areas of Areia Vermelha (AV, impacted area) subjected to different recreational usage. The results indicate that the PEMAV has a disturbed benthic community, with high dominance of a relatively few opportunistic species which are able to tolerate the stress in the area. Gastropoda was the dominant taxon of the macrofauna (98% of total sampled), but <1% of the shells sampled had organisms indicating they were alive when sampled. Caecum ryssotitum and Eulithidium affine were the dominant gastropod species (~30%). Bivalvia, the second most abundant taxon, was dominated by Warrana besnardi and Crassinella lunulata (~90% of bivalvians). There were significant differences (ANOVA; p<0.05) of density and ecological indexes between regions, periods and zones, except for the Shannon index with similar values comparing zones. Community structure of gastropods and bivalvians differed among the factors tested (PERMANOVA; p<0.05), with high similarity comparing AD, sand bank and catamaran areas of AV. The significant changes between the periods were mostly related to differences in the granulometric composition (reef plateau and snorkeling regions) and availability of food resources (AD). In general, the main differences between the reference (AD) and impacted (AV) areas were not related to the high visitation, since they were already found in the period “before”. The spatial and temporal variations in the community were controlled by processes associated to features of the sediment, environmental conditions established through the tidal cycle and anthropic pressure in the area. Although the mechanisms involved in the survival of the organisms need further and more detailed clarification, the low correspondence between dead and live organisms reinforces the necessity to adopt more effective measures for the management of the PEMAV.